Propiedades antitumorales in vitro e in vivo de una ftalocianina de zinc (II) lipofílica para uso en terapia fotodinámica - Chiarante, Nicolás Agustín (2019)
Photodynamic therapy (PDT) is an oncologic treatment that basically consists in the administration of a photosensitizer (PS) that, after activation by visible light in the presence of oxygen, leads to tumor destruction. In order to evaluate the phototoxicity of a new lipophilic phthalocyanine (Pc9), we first selected the most appropriate vehicle. The highest cytotoxic potency was obtained when Pc9 was incorporated into a poloxamine micelle (T1107). We then studied the efficacy of Pc9-T1107 in 2D and 3D cultures of colorectal carcinoma cells (CRC), as well as in an in vivo model of this disease. In vitro, we demonstrated that the effect of Pc9 was mediated by the formation of reactive oxygen species, the permeabilization of lysosomal membrane, the generation of endoplasmic reticulum stress, the depolarization of mitochondrial membrane and finally the induction of an apoptotic cell death. Cell cycle arrest and macroautophagy were also observed. In vivo, we found that Pc9-T1107 decreased tumor growth and prolonged survival time without toxicity signs. In summary, our work leads us to propose Pc9-T1107 as a potential therapeutic agent that could be used, in the near future, for the treatment of CCR.